GENDER CONSTRUCTION IN FAMILY REALITY: A CASE STUDY OF THE ROLE OF POST DIVORCE FAMILY INTERACTIONS IN INDONESIA - Dewi, Kartika Sari; Ginanjar, Adriana; Nugroho, Fentiny; Anggita, Devina (Faculty of Psychology, Universitas Diponegoro, 2023)
The purpose of this study was to highlight the dynamics of gender construction in divorced families. This study used a qualitative method with a case study design on eight mothers-youths from divorced families. In contrast to previous research, this study identified the role of post-divorce family interactions in the construction of gender associated with their well-being. The study’s findings show that the gender scheme developed by youth is linked to patterns of interaction in the family after the parents’ divorce. Changes in parent roles and the presence of extended families contribute to their gender construction. There is an evaluation process that builds an understanding of dynamic gender roles in the family in order to understand the reality of the post-divorce family. Fathers who re-opened communication with their children, mothers as gatekeepers in communication and parenting, and mothers’ and children’s perceptions of the extended family all contributed to the evaluation process. Youth from divorced families face challenges in seeking well-being. They still believe that an intact family is ideal and that the presence of a responsible father is considered important for young people, while the presence of an extended family causes dilemmas in family interactions.